Professional Learning Leading to Perspective and Practice Changes: An Integrated Model for Math Education Professional Development - Kathleen P. King; Judit Kerekes (Adult Education Research Conference, 2010)
The purpose of the action research was to guide the teachers’ practice and development and explore professional results of the approach. This paper presents and analyzes findings from the five teacher participants' interviews, their reflections, and their artifacts/assignments to reveal the scope and nature of the changes using transformative learning as a framework.